2019
DOI: 10.1111/jam.14182
|View full text |Cite
|
Sign up to set email alerts
|

Global proteome response ofSynechocystis6803 to extreme copper environments applied to control the activity of the induciblepetJpromoter

Abstract: Aims Cyanobacteria are prokaryotes performing oxygenic photosynthesis, and they can be engineered to harness solar energy for production of commodity and high‐value chemicals by means of synthetic biology. The Cu2+‐regulated petJ promoter (PpetJ), which controls the expression of the endogenous cytochrome c553, can be used for expression of foreign products in Synechocystis 6803. We aimed to disclose potential bottlenecks in application of the PpetJ in synthetic biology approaches. Methods and Results Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…On the other hand, changes in PSII leads to down-regulation of phycobilisome-related protein expression ( Supplementary Table 1 ). These changes are consistent with previous reports ( Allen et al, 2008 ; Rochaix, 2011 ; Georg et al, 2017 ; Angeleri et al, 2019 ). In addition, the influence of copper or iron limitation on electron transfer will affect the formation of electrochemical gradients of protons inside and outside the TM, which in turn affects the synthesis of ATP by ATP synthase ( Ferguson and Sorgato, 1982 ; Van Walraven et al, 1985 ; Narayan et al, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…On the other hand, changes in PSII leads to down-regulation of phycobilisome-related protein expression ( Supplementary Table 1 ). These changes are consistent with previous reports ( Allen et al, 2008 ; Rochaix, 2011 ; Georg et al, 2017 ; Angeleri et al, 2019 ). In addition, the influence of copper or iron limitation on electron transfer will affect the formation of electrochemical gradients of protons inside and outside the TM, which in turn affects the synthesis of ATP by ATP synthase ( Ferguson and Sorgato, 1982 ; Van Walraven et al, 1985 ; Narayan et al, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…We observed that porins Slr1841, Slr1908, and Slr0042 were significantly down-regulated under copper deduction and iron deduction conditions; Sll1550 was only significantly down-regulated under copper deduction conditions, while Sll1271 was not significantly down-regulated under copper deduction and iron deduction conditions ( Supplementary Table 2 ). This is consistent with previous results regarding copper- or iron-related stress ( Kowata et al, 2017 ; Angeleri et al, 2019 ; Kojima and Okumura, 2020 ). Studies have shown that the deletion of Sll0772, Sll1271, Sll1550, and Slr0042 retarded the growth of Synechocystis 6803 in iron-deficient media ( Qiu et al, 2018 ), suggesting that these porins are associated with iron uptake.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These proteome techniques were employed to study the responses to cold [489]; copper [490]; CO 2 limitation [491]; high light [492]; high or low temperature [469,[492][493][494]; high or low pH [495][496][497]; nitrogen-, phosphate, or sulfate-starvations [481,498,499]; metal stress [498,500,501]; salt stress [502][503][504][505][506][507]; and UV-B stress [508]. They also served to study the tolerance of Synechocystis PCC 6803 to butanol, ethanol, or hexane biofuels [488,[509][510][511][512], as well as to analyze cyanobacterial strains engineered for the production of butanol [511], ethanol [510], hexane [509], or 3-hydroxypropionic acid [513].…”
Section: Responses To Stresses: the Recent Progress In Omics Technicsmentioning
confidence: 99%